2007
DOI: 10.3844/ajabssp.2007.291.298
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of Cr(III) ions by Blue Green-alga Spirulina sp. Part II. Mathematical Modeling

Abstract: In the present paper bioaccumulation of Cr(III) ions by blue-green algae Spirulina sp. is discussed. We found that the process consisted of two stages: passive in which Cr(III) ions are bound to the surface of cells, identical with biosorption and active, metabolism-dependent, in which Cr(III) ions are transported into the cellular interior. The passive stage occurs in both living and non-living cells and the active -only in living biomass. Two distinctive mathematical models of the process were proposed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This is different from the mathematical kinetics model proposed by Chojnacka and Wojciechowski [3] (Equation (17)). Their model shows that the free ions affected the bioaccumulation through the c pas , meaning that metal ions first bonded to cell wall and were then transported into the cytoplasm.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…This is different from the mathematical kinetics model proposed by Chojnacka and Wojciechowski [3] (Equation (17)). Their model shows that the free ions affected the bioaccumulation through the c pas , meaning that metal ions first bonded to cell wall and were then transported into the cytoplasm.…”
Section: Resultsmentioning
confidence: 63%
“…The pseudo-second-order model was well suited for description of the total ion concentration change kinetics, and the equilibrium models were suitable for the description of the cell wall adsorption quantity. There are only a few models describing bioaccumulation in the literature [ 3 ]. A two-step bioaccumulation process was proposed that afforded a quick binding of metal ions to the cell walls, followed by a slower transport process through the cell membrane [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have revealed the mechanism of metal uptake by algae species like blue-green algae Spirulina sp. is chemisorption (chemical adsorption) of metals like chromium and copper other than physical adsorption (Chojnacka and Wojciechowski 2007). Species like Ranunculus trichophyllus, Ranunculus peltatus, Lemna minor, Azolla caroliniana have the potential to serve as arsenic indicators (Favas et al 2012).…”
Section: Introductionmentioning
confidence: 99%